Effects of Ni doping and structural defects on magnetic properties of annealed SiC films. (August 2016) - Fu, Yuting; Jin, Xin; Sun, Ning; Li, Chunjing; An, Yukai; Liu, Jiwen
Abstract: Ni-doped SiC films deposited on Si (100) substrates prepared by RF-magnetron sputtering were discussed in this paper. The results show that with reference to the as-deposited as well as annealing at 800 °C. C atoms were substituted by Ni atoms in the 3CSiC lattice and Ni-related secondary phase cannot be detected. After annealing at 1200 °C, the crystal quality improved obviously while the majority of Ni atoms form the Ni2 Si secondary phase. Temperature dependent on resistivity reveals that the conduction mechanism is dominated by Mott variable range hopping behavior for the Ni-doped SiC films, confirming that the carriers are localized. All the films are ferromagnetic at 300 K and annealing can evidently improve the room-temperature (RT) ferromagnetism. The bound magnetic polarons should be responsible for the RT ferromagnetism of the Ni-doped SiC films. Highlights: There are no reports on room temperature ferromagnetism of Element Ni-doped SiC films. XANES and EXAFS were used as a sensitive method to further investigate the structure. The ferromagnetism is attributed to bound magnetic polarons induced by defects. Phase boundaries between Ni-doped SiC and Ni2 Si make the Ms obviously enhances.